FASE ASPEK PERKEMBANGAN ANAK USIA DINI DALAM KAJIAN AL-QURAN DAN HADITS - Hanita, Hanita (JEA (Jurnal Edukasi AUD), 2020)
Achievement of Education has the aim to form a good personality as an individual and social human being and become a servant of Allah SWT who devotes himself only to Him. Criteria about the abilities achieved by children in all aspects of development - growth consisting of aspects of religion and morals, physical - motor, cognitive, language, social - emotional, and art. The development of the child phase in Islamic religion pays attention to that. Every day activities are arranged and arranged in the study of Al-Quran and Sunnah. In Islam the religion explains that education must be given by humans from an early age. This research is a library research (library research), research that is examined through library research with qualitative data sources of information studied liters and books sources, data collection techniques using primary and secondary data. While the data analysis uses the deductive-inductive method, the comparative method and content analysis. Every aspect is developed in early childhood education with the aim of preparing children to become human beings who are able to carry out their community life well. Along with the book that was revealed by Allah SWT, that is the Koran and Allah also sent the Prophet Muhammad, as Rosullullah who provided guidance and examples for Muslims, all the things he did became a reference for Muslims which we call Al-Hadith. Al-Quran Allah revealed to show, guide, educate and teach humans, get guidance from the truths contained in the Al-Quran about humans.